If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-28=-2(5-8x)
We move all terms to the left:
7x-28-(-2(5-8x))=0
We add all the numbers together, and all the variables
7x-(-2(-8x+5))-28=0
We calculate terms in parentheses: -(-2(-8x+5)), so:We get rid of parentheses
-2(-8x+5)
We multiply parentheses
16x-10
Back to the equation:
-(16x-10)
7x-16x+10-28=0
We add all the numbers together, and all the variables
-9x-18=0
We move all terms containing x to the left, all other terms to the right
-9x=18
x=18/-9
x=-2
| 20+1x=x+44 | | 12=2/3l | | 1+5y=5+4y | | 10(x-3)=x+15 | | 3(4c-2)=15c | | 8x-1=8x-4 | | 5(3x–6)=3(3x–8)+6x | | -5-4x=5x+4 | | x/4=2=6 | | -4w=-9–3w | | w-17=-11+16/w | | 13k−7k=6 | | 41.9=(-22)z | | 24+(9-2x)²=(4x-1)(5+x) | | 5y+32=14y-2 | | v−3=1 | | Y-(-10)=-(x-2) | | 5x3x=-24 | | 15x+1/5=7/15 | | 3x3x=6 | | (-8x-6+8)+(-6x-6+20)=112 | | 4x-2=4(x-2)+6 | | 2.5x-3+2.5x-3=2.5x-3+2.5-3 | | c+5=c+2 | | 18x-104=11x-69 | | 42x+28x=-28+35 | | 1/2(4r-4)-22=-40 | | 2(d-4)2d=9 | | 9.3=0.3t | | -1-8n+5n=7+6n-8n | | 3x=6x+15–8x2.5(x–4)= | | 7x+9=3(x-9) |